Vivencias del paciente con insuficiencia renal crónica en hemodiálisis en un Hospital Público de Trujillo - Amaya Vilca, Eva Lucía (2015)
The work of qualitative research - followed phenomenological concepts of Heidegger, was the object the Experiences of patients with chronic renal failure on hemodialysis about your illness. Done in public hospital Trujillo, 10 participants took part interview being used. Were classified six units of meaning: Inadequate treatment despite knowing about diabetes mellitus type 2, hypertension and other renal diseases causes of chronic renal failure; feelings of sadness and depression at the news of having the disease because you know you never will heal and die anytime; anxiety and fear of complications and side effects, so resignation and acceptance of their illness and move forward in your life as best decision; make a commitment to care by treating and caring for each other for control of the disease and incorporating the hemodialysis machine in your life; the family is an important support for the patient on hemodialysis and believe in God and feel comforted; which were performed for better understanding. The findings reveal that these patients face an uncertain future, but over time his former achieves authenticity withstand taking control of their lives and integrating the disease as part of it.